2012
DOI: 10.1210/jc.2012-2121
|View full text |Cite
|
Sign up to set email alerts
|

Bone Turnover and Bone Mineral Density Are Independently Related to Selenium Status in Healthy Euthyroid Postmenopausal Women

Abstract: Selenium status is inversely related to bone turnover and positively correlated with BMD in healthy euthyroid postmenopausal women independent of thyroid status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
2
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 39 publications
6
72
2
4
Order By: Relevance
“…Similar results were reported by Hoeg et al (17). In a large cohort of postmenopausal women with normal kidney function, they found a negative correlation between SePP and fT4 and fT3 (17).…”
Section: Discussionsupporting
confidence: 89%
“…Similar results were reported by Hoeg et al (17). In a large cohort of postmenopausal women with normal kidney function, they found a negative correlation between SePP and fT4 and fT3 (17).…”
Section: Discussionsupporting
confidence: 89%
“…The proper conduct of these processes translates into the mechanic properties of bones, which is extremely important in the case of stag antlers, used in harem fighting during the mating season [29]. In red deer stags, the growth of antlers usually begins in late winter and early spring, and the increase in the level of testosterone is an initiating signal [30].…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies, deprivation of this micronutrient increased bone resorption and changed bone microarchitecture with a reduction in BMD and bone volume (86,87). Similarly, studies in humans founded that selenium status was inversely related to bone remodeling and positively correlated with BMD in post-menopausal women (88). A case-control study found selenium intake to be inversely associated with reduced risk of osteoporotic hip fracture (89).…”
Section: Seleniummentioning
confidence: 99%